Cardiac Shock Wave Therapy Alleviates Hypoxia/Reoxygenation-Induced Myocardial Necroptosis by Modulating Autophagy. (19th January 2021) - Qiu, Quan; Shen, Tao; Yu, Xiaoxue; Jia, Na; Zhu, Kaiyi; Wang, Que; Liu, Bing; He, Qing
Abstract : Regulated necrosis (necroptosis) is crucially involved in cardiac ischaemia-reperfusion injury (MIRI). The aim of our study is to investigate whether shock wave therapy (SWT) is capable of exerting protective effects by inhibiting necroptosis during myocardial ischaemia-reperfusion (I/R) injury and the possible role of autophagy in this process. We established a hypoxia/reoxygenation (H/R) model in vitro using HL-1 cells to simulate MIRI. MTS assays and LDH cytotoxicity assay were performed to measure cell viability and cell damage. Annexin V/PI staining was used to determine apoptosis and necrosis. Western blotting was performed to assess the changes in cell signaling pathways associated with autophagy, necroptosis, and apoptosis. Reactive oxygen species (ROS) production was detected using DHE staining. Autophagosome generation and degradation (autophagic flux) were analysed using GFP and RFP tandemly tagged LC3 (tfLC3). HL-1 cells were then transfected with p62/SQSTM1 siRNA in order to analyse its role in cardioprotection. Our results revealed that SWT increased cell viability in the H/R model and decreased receptor-interacting serine/threonine-protein kinase 1 (RIPK1) and RIPK3 expression. ROS production was also inhibited by SWT. Moreover, SWT decreased Beclin1 expression and the ratio of LC3-II/LC3-I following H/R. Simultaneously, in the tfLC3 assay, the SWT provoked a decrease in the cumulative autophagosome abundance. siRNA-mediated knockdown of p62 attenuated H/R-induced necroptosis, and SWT did not exert additive effects. Taken together, SWT ameliorated H/R injury by inhibiting necroptosis. SWT also relieved the blockade of autophagic flux in response to H/R injury. The restoration of autophagic flux by SWT might contribute to its cardioprotective effect on necroptosis following H/R injury.